Volatile Urinary Signals of Two Nocturnal Primates, Microcebus murinus and M. lehilahytsara - Caspers, Jana; Radespiel, Ute; Zimmermann, Elke; Schulz, Stefan (Frontiers in Ecology and Evolution, 2020)
Mouse lemurs are small, nocturnal, arboreal solitary foragers and are endemic primates of Madagascar. This lifestyle and their high predation risk can explain why mouse lemurs rely heavily on olfaction for intraspecific communication. As they often use urine for this purpose, we investigated dichloromethane extracts of the urine of two mouse lemur species, the gray mouse lemur (Microcebus murinus) and the Godman’s mouse lemur (M. lehilahytsara), using gas-chromatography-mass spectrometry. We detected 977 different volatile compounds of different compound classes in 22 urine extracts obtained from nine M. murinus (four males, five females) and nine M. lehilahytsara (three males, six females) individuals. We compared the volatile profiles of the sexes and species using principal component analyses and discriminant function analyses and detected a significant difference in the urinary profiles of males and females and in the profiles of M. murinus and M. lehilahytsara. These very complex sex- and species-specific signatures could be used for distance communication in the context of species recognition, for mate search and in male-male competition. Our study provides important mechanistic insights into complex chemical signaling pathways in primates that are mirrored, in the case of mouse lemurs, by their extraordinarily rich repertoire of olfactory receptors. The production of highly informative olfactory signals may be complementing the complex acoustic signaling system of these solitary foragers suggesting the existence of a multimodal communication network that should be highly beneficial for any species living in dispersed social networks.